Change of Direction and Agility Tests: Challenging Our Current Measures of Performance. Issue 1 (February 2018) - Nimphius, Sophia; Callaghan, Samuel J.; Bezodis, Neil E.; Lockie, Robert G.
Abstract : ABSTRACT: THE ABILITY TO CHANGE DIRECTION IS A HIGHLY VALUED ATHLETIC QUALITY IN SPORT AND HAS BEEN MEASURED EXTENSIVELY. DESPITE THE IMPORTANCE AND MAGNITUDE OF RESEARCH ON CHANGE OF DIRECTION (COD) AND AGILITY, THE VALIDITY OF THE PERFORMANCE MEASURES USED TO ASSESS THESE ABILITIES HAVE FACED LIMITED SCRUTINY. A CRITICAL EVALUATION OF OUR CURRENT MEASURES OF COD AND AGILITY ARE PRESENTED. FURTHERMORE, A SUMMARY OF RECOMMENDATIONS TO ENHANCE THE VALIDITY OF COD AND AGILITY ASSESSMENT IS PROVIDED IN THE ULTIMATE EFFORT TO IMPROVE OUR UNDERSTANDING OF THIS CRUCIAL ATHLETIC QUALITY. A VIDEO ABSTRACT DESCRIBING THIS ARTICLE CAN BE FOUND IN SUPPLEMENTAL DIGITAL CONTENT 1 (SEE VIDEO, http://links.lww.com/SCJ/A217 ). Abstract : Supplemental Digital Content is Available in the Text.